Traumatic Diaphragmatic Rupture Leading to Tension Gastrothorax: A Critical Case Report and Surgical Insight - WIlopo, Ivor Wiguna Hartanto (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Traumatic diaphragmatic rupture (TDR) is a serious but relatively uncommon injury, often resulting from blunt trauma, particularly motor vehicle accidents. Among these, blunt TDR presents with more severe outcomes than penetrating injuries, including higher mortality rates. A life-threatening complication of TDR is gastrothorax, which occurs when the stomach herniates into the thoracic cavity, leading to elevated intrathoracic pressure and potentially fatal consequences such as respiratory failure or cardiac arrest. This case reported a 23-year-old male who sustained a motor vehicle collision, presenting with progressive shortness of breath, nausea, and vomiting 15 hours post-injury. Imaging confirmed a diaphragmatic rupture with associated tension gastrothorax. Immediate intervention with nasogastric tube placement provided symptom relief, followed by exploratory laparotomy to repair the diaphragmatic defect. The patient's recovery was uneventful, demonstrating the critical importance of early diagnosis and timely surgical management in cases of TDR with gastrothorax. Traumatic diaphragmatic rupture occurs in approximately 0.8–1.6% of trauma cases, with motor vehicle accidents being the leading cause. Due to its potential for delayed diagnosis, the rupture is often missed initially, leading to higher rates of morbidity and mortality. Early detection is critical, as it can prevent serious complications such as bowel herniation into the thoracic cavity, respiratory distress, or even death.